Changes to the Regulatory Framework of the Chinese Rare Earth Industry after the Global Financial Crisis - Roland Howanietz (The Copenhagen Journal of Asian Studies, 2017)
In the wake of the Global Financial Crisis, the Chinese government radically adjusted the regulatory framework of the domestic Rare Earth Elements (REEs) sector. This article investigates the reasons for regulatory adjustments and the impact on China's market power. The analysis of long-term REEs price and production trends illustrates four reasons for regulatory adjustments: the China discount, the need for industrial upgrading, growing domestic REEs demand and severe environmental pollution. The analysis of the effects of regulations shows that the restrictive trade regime has increased China's market power and ability to affect prices, which led to a redistribution of global welfare in favour of China. However, this market power is only temporary due to foreign countermeasures such as WTO-based allegations.